Production of powder yeast starter culture for fermentation of cocoa beans - Chanprasartsuk, On-ong; Seethong, Pichaya; Paijit, Watchaphon (Food Agricultural Sciences and Technology, 2026)
The unique flavor and aroma of cocoa beans are derived from the spontaneous fermentation with natural microorganisms, where yeast is the primary microorganism found during the initial period of fermentation. However, the natural fermentation process may cause variations in the quality of cocoa beans. The powdered starter culture of Saccharomyces yeast was produced for cocoa fermentation. The inoculums were prepared and dried at 40 oC for 14, 15, and 16 hours, and 45 oC and 50 oC for 7, 8, and 9 hours, respectively. Liquid starter culture fermentation was used as a control. The powder yeast starter culture was dried at 40 oC for 15 hours with a moisture content of < 8.5% (w/w) and the maximum survival of the yeast population (P < 0.05) was used for small-scale cocoa fermentation. The cut test results showed that the powdered starter culture could complete cocoa fermentation with a consistent quality of cocoa beans. To improve the quality of powdered starter cultures and better understand the role of powdered yeast inoculum on the quality of cocoa beans, the shelf life of powdered starter cultures and the chemical composition of cacao beans after fermentation with powdered starter cultures were further investigated.